2019
DOI: 10.2478/eko-2019-0013
|View full text |Cite
|
Sign up to set email alerts
|

Floristic Biodiversity of Weed Communities in Arable Lands of Istria Peninsula (From 2005 to 2017)

Abstract: Štefanić E., Kovačević V., Antunović S., Japundžić-Palenkić B., Zima D., Turalija A., Nestorović N.: Floristic biodiversity of weed communities in arable lands of Istria peninsula (from 2005 to 2017). This paper analyses the floristic biodiversity of weed communities in the arable lands of the Istrian peninsula during a twelve year period (2005−2017). A total of 50 fields were surveyed for each sampling time using the seven-degree Braun-Blanquet cover abundance scale in the following agricultural categories: a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Furthermore, any potential human-caused disturbance can significantly change the habitat quality via the cascading effects on biophysical structure and function [67]. Only a few plants can cope with different forms of disturbance, and plant with high dispersal ability and smaller growth forms usually become dominant species in severe disturbed urban area [68,69], which was also found in our study that small growth forms has greater a percentage in higher urbanization regions. Thus the community types were fewer in the center of urban.…”
Section: Causes Of Ruderal Community Diversitysupporting
confidence: 68%
See 1 more Smart Citation
“…Furthermore, any potential human-caused disturbance can significantly change the habitat quality via the cascading effects on biophysical structure and function [67]. Only a few plants can cope with different forms of disturbance, and plant with high dispersal ability and smaller growth forms usually become dominant species in severe disturbed urban area [68,69], which was also found in our study that small growth forms has greater a percentage in higher urbanization regions. Thus the community types were fewer in the center of urban.…”
Section: Causes Of Ruderal Community Diversitysupporting
confidence: 68%
“…The rhizomes of ruderals are potentially independent, can maintain a constantly updated state in urban habitats with severe human disturbance, and they can occupy large areas of habitat and form communities. Moreover, they hinder the survival of other species, thus forming a single dominant species community [41,69]. Wind transmission can also sexually propagate the granular seeds of ruderals.…”
Section: Causes Of Ruderal Community Diversitymentioning
confidence: 99%
“…In the Republic of Croatia weed flora in arable lands have changed over past several decades (Radojčić et al, 2018;Štefanić et al, 2019). Some species are declining in their abundance, whereas others have increased (Štefanić et al,2018).…”
Section: Discussionmentioning
confidence: 99%
“…Agricultural intensification has been identified as the main cause of agrobiodiversity loss (Storkey and Westbury 2007;Potts et al 2010;Meyer et al 2013). Several studies have shown that intensive arable farming negatively affects arable plant communities in terms of their biodiversity as well as the ecosystem services they provide (Marshall et al 2003;Meyer et al 2015;Chamorro et al 2016;Štefanić et al 2019;Görzen et al 2021). The recognition of the importance of the segetal flora for agroecosystems supporting a diverse fauna and beneficial microorganisms has focused attention on the need to maintain traditionally cultivated habitats (Storkey and Neve 2018;Mupepele et al 2019;Böhning-Gaese et al 2020;Bourgeois et al 2020;Gaba et al 2020).…”
Section: Introductionmentioning
confidence: 99%